THE EFFECT OF STATIC MAGNETIC FIELD EXPOSURE ON BODY WEIGHT AND ADIPOSE CELLS DENSITY OF OBESE MICE - Puji Sari; luluk yunaini; Widia Bela Oktaviani; Umiatin Umiatin; Anita Dwi Suryandari (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Obesity is a mojar public health problem in worldwide, especially in Indonesia. Obesity in addition to affecting productivity, is also trigger for other chronic disease such as diabetes and cardiac disease. Body mass index is an assessment tool used to assess degree of individual adiposity to define overweight, obesity, and severe obesity.The determination of obesity is based on the calculation of Body Mass Index (BMI), which devide body weight (kg) by height (cm2). In addition to the method of regulating diet, exercise, and bariatric surgery for weight loss, it was reported that the biophysical therapy tool, that is static magnetic field (SMF) became a modality for weight loss. Based on research reports, it proves that the static magnetic field affects weight loss in the group of obese mice after 30 days of exposure. Therefore, in this study, we carried out static magnetic field exposure to obese mice with a field intensity of 2 mT for 1 hour/day. Mice were exposed gradually to SMF on 2, 7, 14, and 21 days to determine the effectiveness of SMF to obesity in mice in terms of weight loss and cellular adipose cell density. The results showed that the weight of mice decreased significantly on 2nd and 7th days of exposure, the trend showed a decrease in body weight until the 14th day. The density of adipose tissue is increased after exposure to SMF on the 14th and 21st days of exposure. It showed that early exposure to SMF (2 and 7 days) could induce weight loss in mice, while cellularly SMF increased adipose cell density on late exposure (14 and 21 days).